2000
DOI: 10.1016/s0735-1097(00)00608-2
|View full text |Cite
|
Sign up to set email alerts
|

Effective prevention of atrial fibrillation by continuous atrial overdrive pacing after coronary artery bypass surgery

Abstract: We conclude that continuous atrial pacing with an algorithm for dynamic overdrive reduces significantly incidence of AF the second day after CABG surgery, particularly in patients with preserved left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 20 publications
0
56
0
2
Order By: Relevance
“…Atrial pacing, on the other hand, was a predictor of freedom from developing AF, which is in accordance with previous observations. 14,15 The incidence of postoperative AF was higher with the use of dopamine and dobutamine, both of which are predominantly ␤ 1 -adrenergic receptor agonists, compared with phenylepherine, which in therapeutic doses is predominantly an agonist of ␣-adrenergic receptors and lacks direct stimulatory effects on atrial myocardium. In fact, the prevalence of AF in patients in whom phenylepherine was used was similar to those in whom no adrenergic drug was used.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial pacing, on the other hand, was a predictor of freedom from developing AF, which is in accordance with previous observations. 14,15 The incidence of postoperative AF was higher with the use of dopamine and dobutamine, both of which are predominantly ␤ 1 -adrenergic receptor agonists, compared with phenylepherine, which in therapeutic doses is predominantly an agonist of ␣-adrenergic receptors and lacks direct stimulatory effects on atrial myocardium. In fact, the prevalence of AF in patients in whom phenylepherine was used was similar to those in whom no adrenergic drug was used.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53][54][55][56][57][58][59][60][61] These trials were small, varying in size of treatment groups from 9 to 100 patients. Treatment protocols used different locations of pacing electrodes (right atrial, 51-57 left atrial, 54,57 and biatrial pacing.…”
Section: Pacingmentioning
confidence: 99%
“…Trials also differed in pacing algorithms; some used simple overdrive at a fixed heart rate, 53,55,59 and others used more complex overdrive algorithms. 51 …”
Section: Pacingmentioning
confidence: 99%
“…[20][21][22][23] Recently, several reports have shown that multisite temporary atrial pacing via epicardial electrodes placed during surgery might be effective in preventing postoperative AF. [24][25][26][27][28][29][30][31][32] In a double-blind, randomized study, Daoud et al evaluated the effects of different pacing modes in 118 patients who had undergone open heart surgery. 28 In this study, patients were randomized to one of the following three groups: right atrial pacing with an inhibited mode at a rate of 45 beats/min; right atrial overdrive pacing with a triggered mode ≥ 10 beats greater than the patient's intrinsic (but not < 85 beats/min) rate; and biatrial overdrive pacing with a triggered mode ≥ 10 beats greater than the patient's intrinsic (but not < 85 beats/min) rate.…”
Section: Discussionmentioning
confidence: 99%